Becoming a critical thinker : for your university studies and beyond - Ivory, Sarah Birrell (Oxford, United Kingdom ; New York, NY : Oxford University Press, 2021)
'Join Sarah Ivory as she helps you to explore these two fundamental questions, guiding you at every step in her clear, personable, and honest style. Becoming a Critical Thinker offers unique insights from real students and professionals to inspire you; guided reflections, exercises, and checklists to help you develop your skills in a hands-on way; and tried-and-tested frameworks to apply those skills for success in your studies and beyond. This is the ideal guide for anyone looking to improve their thinking on their journey to becoming an effective student, professional, or global citizen'--
Includes bibliographical references (311-314) and index.
Keywords: Critical thinking -- Study and teaching (Higher); Thought and thinking; Academic achievement